Neurodevelopmental and health‐related quality‐of‐life outcomes in adolescence after surgery for congenital heart disease in infancy. (25th April 2019) - Wotherspoon, Jane M; Eagleson, Karen J; Gilmore, Linda; Auld, Benjamin; Hirst, Anne; Johnson, Susan; Stocker, Christian; Heussler, Helen; Justo, Robert N
Abstract : Aim: To assess outcomes in adolescence after surgery for congenital heart disease (CHD) in infancy. Domains analysed included cognition and executive function, social and emotional well‐being, adaptive behaviour, academic achievement, and health‐related quality of life (HRQoL). Method: Twenty‐one participants (10 males, 11 females) ranged in age from 14 to 17 years (mean 15y 4.8mo, SD 8.4mo). Twenty had biventricular repairs. All were classified as New York Heart Association class I. Measures included: Wechsler Intelligence and Achievement scales; Wide Range Assessment of Memory and Learning, Second Edition; California Verbal Learning Test – Children's Version; Behaviour Rating Inventory of Executive Function; Conners, Third Edition; Adaptive Behavior Assessment System, Second Edition; Behavior Assessment System for Children, Second Edition; Rey–Osterrieth Complex Figure; and Pediatric Quality of Life Inventory. Results: Outcomes were significantly lower ( p≤ 0.01) than population norms for processing speed, mathematical achievement, attention, and visual–spatial ability. Participants reported more frequent learning problems but more positive family relations. HRQoL was significantly lower across most domains by self‐ and parent‐proxy report. Interpretation: Individuals with CHD may experience difficulties across a range of domains. These findings emphasize the importance of comprehensive screening, early intervention, and long‐term follow‐up, as deficits may extend into young adulthood. What this paper adds: Identified cognitive, learning, and attentional impairments in adolescents after congenital heart disease surgery in infancy. Combined self‐report, caregiver report, and laboratory tasks in a comprehensive neurodevelopmental assessment protocol. Health‐related quality of life was lower across most domains. What this paper adds: Identified cognitive, learning, and attentional impairments in adolescents after congenital heart disease surgery in infancy. Combined self‐report, caregiver report, and laboratory tasks in a comprehensive neurodevelopmental assessment protocol. Health‐related quality of life was lower across most domains.